Determining parameters of blasting operations at coal open pit mines based on the results of production trial tests and studies - Surmaajav, D.; Lhaikhansuren, B. (Eximia, 2021)
Nowadays, the role of physical and chemical processes in the mining industry is increasing. New mining technologies and advanced research methods have been developed and widely used, studying various properties of rock mass/ massif, such as structure, strength, elasticity, and acoustics etc. Rock massif of coal deposits, mostly presented by layered rocks of sedimentary origin is divided by various joints and fractures, that directly affects blasting results. This study aims to determine the basic parameters of blasting operations in specific mining-geological conditions based on the rock strength and average size of natural particles in the rock massif, since intensity of joint system and physical and mechanical properties of rock massif depend on thickness of natural particles in the rock massif.